(untitled) (Fiep Bulletin - online, 2014)
The studies on body image have increased significantly in the past decade. This study intended to identify the body image assessment protocols used in academic and scientific research studies in Brazil in the last 15 years. Ninety-nine protocols were analyzed in 60 scientific articles made available in free online databases - Bireme, Medline, Lilacs, Google, Scielo and Usp. The protocols were separated into 6 groups: Questionnaires, 27%; Interviews, 30%; Drawings and Anthropometric Variables, 15% each; Scales, 9%; and Silhouettes, 4%. The researchers sought for a non-limited methodology which could best be applied in the group being studied and which resulted in a number of optional tools to assess body image.